The Impact of Nasal Surgery on Sleep Quality: A Prospective Outcomes Study. (November 2014) - Stapleton, Amanda L.; Chang, Yue-Fang; Soose, Ryan J.; Gillman, Grant S.
Objective: (1) Evaluate the impact of nasal airway surgery on sleep quality using validated outcome measurements, (2) compare the utility of Epworth Sleepiness Scale (ESS) versus Pittsburgh Sleep Quality Index (PSQI) as a reflection of sleep quality, and (3) identify perioperative variables that might correlate with a beneficial effect of nasal surgery on sleep quality. Study Design: Prospective outcome study of patients with symptomatic nasal obstruction undergoing nasal airway surgery. Setting: Academic medical center. Methods: Patients completed the Nasal Obstruction Symptom Evaluation (NOSE) scale, ESS, PSQI, and Ease-of-Breathing and Sleep Quality Likert scales preoperatively and 3 months postoperatively. A nonparametric analysis compared pre- and postoperative values, and associations were examined using Spearman correlations. Results: Sixty-one patients completed the study. Mean NOSE scores decreased significantly from 68.2 preoperatively to 17.5 three months after surgery. Mean ESS scores and PSQI scores improved ( P < .0001) over that same interval (7.5 to 5.3 and 7.8 to 4.6, respectively). There was a correlation seen between the degree of change in both NOSE scores and Ease-of-Breathing scores and the change in sleep quality measured using the PSQI or Sleep Quality Likert scores. The PSQI correlated better with Sleep Quality Likert scores than the ESS. Overall, 86.9% of subjects reported subjective improvement in sleep quality postoperatively. Conclusion: In patients undergoing nasal airway surgery there may be a secondary improvement in subjective sleep quality. The degree of change in sleep quality correlates with the severity of nasal obstruction preoperatively and the degree of improvement in obstruction with surgery.